RNF34 modulates the mitochondrial biogenesis and exercise capacity in muscle and lipid metabolism through ubiquitination of PGC-1 in Drosophila. - Wei, P.; Guo, J.; Xue, W.; Zhao, Y.; Yang, J.; Wang, J. (Acta Biochimica Biophysica Sinica [Zhongguo ke xue yuan], 2018)
The transcriptional co-activator PGC-1? is a key regulator of mitochondrial function and muscle fiber specification in the skeletal muscle. The E3 ubiquitin ligase RNF34 ubiquitinates PGC-1? and negatively regulates mammalian brown fat cell metabolism. However, the functional importance of RNF34 in the skeletal muscle and its impact on energy metabolism remain unknown. The Drosophila PGC-1 homolog dPGC-1 and its mammalian counterparts have conserved functions in mitochondria and insulin signaling. Here, we showed that the Drosophila RNF34 (dRNF34) ubiquitinates the Drosophila PGC-1? (dPGC-1) and promotes its degradation in HEK293T cells by immunoprecipitation and western blot analysis. This allows us to use Drosophila as a powerful model system to study the physiological role of RNF34 in mitochondrial function and metabolism. In the in vivo studies, by separately expressing two independent UAS-dRNF34 RNAi transgenes driven by the muscle-specific 24B-Gal4 driver, we found that knockdown of dRNF34 specifically in muscle promotes mitochondrial biogenesis, improves negative geotaxis, extends climbing time to exhaustion in moderate aged flies and counteracts high-fat-diet-induced high triglyceride content. Furthermore, we showed that knockdown of dPGC-1 reversed the effects of the dRNF34 knockdown phenotypes described above. Our results reveal that dRNF34 plays an important role in regulating mitochondrial biogenesis in muscle and lipid metabolism through dPGC-1. Thus, inhibition of RNF34 activity provides a potential novel therapeutic strategy for the treatment of age-related muscle dysfunction.